Unifying the Romanization of Geographical Names in the Arab World Using Classical Arabic - Al-Rawashdeh, Sukinh Yousef (Journal of Ecohumanism, 2025)
This study aims to address the issue of standardizing the Romanization of geographical names in the Arab world using classical Arabic. This issue is increasingly important in light of the need for linguistic compatibility and standardization when naming and converting geographical locations to Latin letters. Linguistic differences, local dialects, and variations in writing styles among Arab countries are major obstacles to the standardization of Romanization, leading to significant variations in how geographical names are written when translated into other languages, especially in academic, geographical, and official contexts. The study reviews previous efforts to establish unified standards for Romanization in some Arab countries. It discusses current systems, such as the BGN/PCGN system and the system used in the United Nations, focusing on the strengths and weaknesses of each system. The study adopts a comparative analytical methodology, as it analyzes several geographical names in various Arab countries according to the currently used systems and presents a proposed model for the standardization of Romanization based on the rules of the classical Arabic language. Taking into account the phonetic and linguistic characteristics that reflect correct Arabic pronunciation. A group of geographical names from various Arab countries was studied, and the proposed model was tested. The results were analyzed and compared with existing systems. The results demonstrated that the proposed model provides a high degree of accuracy in translating Arabic sounds into Latin, which reduces differences and enhances the clarity and accuracy of geographical names when used in maps and international documents. The study concludes with a recommendation to adopt the proposed model as a unified framework for the Romanization of geographical names in the Arab world, given its practical benefits in improving transliteration and enhancing international understanding. This contributes to achieving greater cohesion in Arab geography at the global level. The study also recommends conducting further field research to apply the proposed model on a broader scale and analyze its results more deeply.